THE INFLUENCE OF THE WORDWALL-BASED TEAMS GAMES TOURNAMENT (TGT) MODEL ON LEARNING OUTCOMES IN BUILDING MATERIAL CLASSROOM V SD - Ms. Tri Noviana; Mr. Ramanata Disurya; Mr. Farizal Imansyah (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research is about the influence of the wordwall-based Teams Games Tournament (TGT) model on the learning outcomes of class V elementary school classroom material, with the hope of increasing understanding of mathematics learning through the application of the TGT learning model supported by wordwall media. The formulation of the problem is whether there is an influence of the wordwall-based Teams Games Tournament (TGT) model on the learning outcomes of class V elementary school classroom material. The aim of the research is to determine the effect of the wordwall-based Teams Games Tournament (TGT) model on learning outcomes for class V elementary school building materials. The research method used was an experiment with a quantitative approach. This research uses a True Experimental Design, namely posttest only control design. The research subjects consisted of two classes, namely class V.A and class V.C with a total of 62 students. Data collection techniques are carried out through test techniques and documentation. Data analysis techniques were carried out using normality tests, homogeneity tests, and hypothesis tests. Hypothesis testing uses the independent sample t-test. The results of the hypothesis analysis show that the value of ????ℎ???????????????????? is 5.849, exceeding the value of ???????????????????????? of 1.670, with a significance level of <0.05 (0.000-0.05). Thus, it can be concluded that the use of the Wordwall-based Teams Games Tournament (TGT) Model is suitable for application in learning and has a significant influence.